MEMORY REQUIREMENTS FOR HARDWARE IMPLEMENTATION OF THE H.264 ENCODER MODULES - MESSAOUDI, KAMEL.; BOURENNANE, EL-BAY; TOUMI, SALAH; LABBANI, OUASSILA (Courrier du Savoir; Vol. 14 (2012): Courrier du Savoir, 2014)
For a hardware implementation of any image processing algorithm, it is necessary to study the input/output of each processing module  even  before  studying  the  internal  architecture  of  these modules. And  that  to  prepare  a  simulation  platform, with internal and external memory, necessary  to  load and  to prepare  the  input  for  the modules. These memories are also used as intermediate  component  between  the  different modules  to  provide  the  possibility  of  parallelism.  In  this work we  give  the architecture  of  internal  and  external  memory  used  by  the  H.264  encoder  in  order  to  develop  a  simulation  platform  for processing modules. This platform can be realized in FPGA platform chosen according to the memory requirements.